The Socio-Cultural Role Of Musical Dances Among The Vatsonga (Journal of Namibian Studies : History Politics Culture, 2023)
This paper attempts to offer a detailed appraisal of Xitsonga musical world – the significance, performances as well as the circumstances under which they take place.   The discussion of songs in this study focuses on Xitsonga songs which serve critical and remarkable roles in the life experiences of the Vatsonga.  In carrying out the research, interviews and observation were necessary as the researcher had to be present when performances took place. These primary research methods were complemented by information from books and articles on the subject under consideration. It was found that the Vatsonga have a peculiar way of doing things embedded in their cultural traditions. It was also found that these traditions are slowly vanishing since they are, these days, only valued and remembered by the elderly. The fact that music is a powerful asset in invoking emotions and action was also observed by the researcher.